The power of listening active listening what it is and how it affects total communication - The Open University BBC TV ([United Kingdom] : The Open University, 1971)
Being a good listener is one of the most important aspects of effective communication, but it is also seems to be one of the most difficult for people to practice. Learning to listen well can help individuals to improve their academic performance, foster better friendships, and to be better employees in the workplace.
Converted into VHS 1/2 in. and DVD
filem 20 AS122.06.M201
Bahan rosak (Lupus)
Keywords: Listening; Hearing